De "Problema" à dissidência: os marcadores sociais da diferença e a construção das identidades sociais de estudantes das séries finais do ensino fundamental numa escola pública de Uruguaiana/RS - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This study investigated the construction of the identity of students considered "problematic" by the school community, based on criteria such as low academic performance, indiscipline, and remedial classes. The research used a qualitative approach and case study methodology, involving 7th-grade students from a public school in Uruguaiana/RS. The results indicated that the notion of a "problem-student" is influenced by social markers of difference, such as gender, race, and class, and reflects tensions between school values and students' symbolic universes, suggesting that what is perceived as a "problem" may actually be understood as dissidence.
From "Problem" to dissidence: the social markers of difference and the construction of social identities of students in the final grades of elementary school in a public school of Uruguaiana/RS
Keywords: Public education; Social markers of difference; Indiscipline; Elementary education; Marcadores sociais da diferença; Identity; Ensino fundamental; Educação pública; Identidade; Indisciplina; CNPQ::CIENCIAS HUMANAS